Further evidence for aberrant prefrontal salience coding in schizophrenia - Walter, Henrik; Heckers, Stephan; Kassubek, Jan; Erk, Susanne; Frasch, Karel; Abler, Birgit (Frontiers in Behavioral Neuroscience, 2010)
The revised dopamine hypothesis of schizophrenia postulates that dopamine metabolism is impacted differently with increased dopamine in the subcortical mesolimbic system and decreased dopamine in prefrontal cortical regions. Recently, we described findings supporting this hypothesis using a financial reward task in patients with schizophrenia (Walter et al. 2009). In addition to analysing prediction and prediction error coding, we found in this study evidence for aberrant cortical representation of salience in the right ventrolateral prefrontal cortex (VLPFC) in patients. Here, we reanalysed data of four other published reward studies of our group in order to investigate (i) whether we could replicate this finding in an independent cohort of patients with schizophrenia and (ii) how dopaminergic modulation impacts on cortical salience representation. Our main result was that we could replicate the finding of aberrant salience coding in the right VLPFC in patients with schizophrenia. Furthermore, we found evidence that the degree of salience coding in this region was correlated inversely with negative symptoms (anhedonia). Results of dopaminergic modulation showed tentative evidence for an influence of dopaminergic stimulation, but were not conclusive. In summary, we conclude that the right VLPFC might play a crucial role in salience coding and is impaired in schizophrenia.